Unilateral undescended testis with a contralateral “over-descended testis” present in a left groin interstitial hernia presenting in mid-adulthood - Jarrod P. Kaufman; Jacob Levy; David Chen; Yuri Novitsky (International Journal of Abdominal Wall and Hernia Surgery)
Hernia repair remains one of the most common operative procedures performed by general surgeons and herniologists (hernia specialists). Congenital or acquired hernias fall into predictable categories: inguinal, ventral or abdominal, and incisional. Inguinal hernias are the most common accounting for roughly 70% of all hernias. Ventral, abdominal, and incisional hernias are interrelated and their prevalence varies. Other obscure or less common types of hernias include interparietal, obturator, femoral, and interstitial, and their prevalence is around 1%–2% at most. During our operative week, a unique patient presented for evaluation. Until that moment, our team of United States-based adult and pediatric surgeons lacked exceptional first-hand experience with inguinal interstitial hernias. These are generally recognized after previous abdominal wall trauma or surgeries as well as in the setting of congenital defects due to a testis that has not descended. Here, we present a rare case of an inguinal interstitial hernia containing an undescended left testicle that traversed through the internal ring, pivoting lateral and passing parallel to the inguinal canal and into the superficial thigh. Along its course, it traveled through the abdominal wall fascia protruding into the lower extremity, followed by the fascia lata, allowing the testicle and the hernia sac to reside in the left lower extremity thigh anterior compartment.